Physicians’ Well-Being Linked To In-Basket Messages Generated By Algorithms In Electronic Health Records - Tai-Seale, Ming; Dillon, Ellis C.; Yang, Yan; Nordgren, Robert; Steinberg, Ruth L.; Nauenberg, Teresa; Lee, Tim C.; Meehan, Amy; Li, Jinnan; Chan, Albert Solomon; Frosch, Dominick L. (Health Affairs, 2019)
Despite concerns about physicians' workload associated with electronic health records (EHRs), little attention has been paid to the relationship between physicians' well-being and the in-basket messages physicians receive-specifically, their volume and sources. Analyses of EHR work performed by physicians in a multispecialty practice found that in-basket messages generated by the EHR system accounted for almost half (114) of the 243 weekly in-basket messages received per physician, on average-far exceeding the numbers received from their colleagues (53) and patients (30). In a survey, 36 percent of the physicians reported burnout symptoms, and 29 percent intended to reduce their clinical work time in the upcoming year. Receiving more than the average number of system-generated in-basket messages was associated with 40 percent higher probability of burnout and 38 percent higher probability of intending to reduce clinical work time. Physicians' perceptions of a positive work environment were associated with lower odds of burnout and intention to reduce clinical work time and with greater satisfaction with life. Female physicians had a higher risk of burnout and lower satisfaction with life, compared to males. Meaningful redesign of EHR in-basket workflow and a wellness-enhancing work environment are necessary to effectively improve physicians' well-being.